Influence of Soil Colloids on the Transport of Cd2+ and Pb2+ under Different pH and Ionic Strength Conditions - Zihao Ye; Dihao Xu; Jiawen Zhong; Shuang Gao; Jinjin Wang; Yulong Zhang; Huijuan Xu; Yongtao Li; Wenyan Li (Agronomy, 2024)
The co-transport of contaminants by soil colloids can generate substantial environmental risk, and this behavior is greatly affected by environmental conditions. In this study, AF4-ICP-MS was used to investigate the size distribution and composition of Cd/Pb-bearing colloids; saturated sand column experiments were used to investigate the impact of soil colloids on the transport of Cd/Pb under different pH and ionic strength conditions. AF4-ICP-MS characterization showed that natural colloids were primarily associated with two sizes ranges: 0.3–35 KDa (F1, fine nanoparticles) and 280 KDa–450 nm (F2, larger nanoparticles), which mainly consisted of organic matter (OM), iron (Fe), and manganese (Mn) (oxy)hydroxides and clay minerals. Fine nanoparticles could strongly adsorb Cd and Pb under all environmental conditions. Mn and Fe (oxy)hydroxides generally formed under neutral to alkaline conditions and exhibited adsorption capabilities for Cd and Pb, respectively. Transport experiments were conducted under different pH and ionic strength conditions. At pH 3.0, soil colloids had little effect on the transport of Cd2+ and Pb2+. At pH 5.0, soil colloids inhibited the transport of Cd2+ by 16.1%, and Pb2+ recovery was still 0.0%. At pH 7.0 and 9.0, soil colloids facilitated the transport of Cd2+ by 15.6% and 29.6%, facilitated Pb2+ by 1.3% and 6.4%. At an ionic strength of 0, 0.005, and 0.01 mol L−1 NaNO3, soil colloids facilitated the transport of Cd2+ by 77.7%, 45.8%, and 15.6%, only facilitated the transport of Pb2+ by 46.2% at an ionic strength of 0 mol L−1 NaNO3. At an ionic strength of 0.05 mol L−1 NaNO3, soil colloids inhibited the transport of Cd2+ and Pb2+ by 33.1% and 21.0%, respectively. The transport of Cd2+ and Pb2+ facilitated by soil colloids was clearly observed under low ionic strength and non-acidic conditions, which can generate a potential environmental risk.